2019
DOI: 10.1371/journal.pone.0222531
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen surveillance in the informal settlement, Kibera, Kenya, using a metagenomics approach

Abstract: BackgroundWorldwide, the number of emerging and re-emerging infectious diseases is increasing, highlighting the importance of global disease pathogen surveillance. Traditional population-based methods may fail to capture important events, particularly in settings with limited access to health care, such as urban informal settlements. In such environments, a mixture of surface water runoff and human feces containing pathogenic microorganisms could be used as a surveillance surrogate.MethodWe conducted a tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…Longitudinal studies demonstrating a human-wastewater AMR correlation typically included longer sampling intervals (six months versus two months for negative/inconclusive studies) and timeframes. For the highest resolution sampling campaigns 26,40 which used two week sampling intervals across different timeframes, one study observed an association between ampicillin-resistant wastewater and contemporaneous clinical isolates over 12 months, whereas the other found changes in metagenomic read abundances were not matched by changes in contemporaneous clinical surveillance over three months. Directly comparing these studies is difficult due to different methodologies, but the findings would support the fact that studies sampling over a timeframe of ≥6 months are more likely to capture associations with human population-level AMR (Fig.3B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal studies demonstrating a human-wastewater AMR correlation typically included longer sampling intervals (six months versus two months for negative/inconclusive studies) and timeframes. For the highest resolution sampling campaigns 26,40 which used two week sampling intervals across different timeframes, one study observed an association between ampicillin-resistant wastewater and contemporaneous clinical isolates over 12 months, whereas the other found changes in metagenomic read abundances were not matched by changes in contemporaneous clinical surveillance over three months. Directly comparing these studies is difficult due to different methodologies, but the findings would support the fact that studies sampling over a timeframe of ≥6 months are more likely to capture associations with human population-level AMR (Fig.3B).…”
Section: Discussionmentioning
confidence: 99%
“…Only 2/6 indirect studies reported significant relationships compared to 4/9 direct studies. Smaller catchments also limit sample sizes potentially obscuring signals from detection which may have contributed to unclear/negative outcomes 40 . When comparing direct studies, similar sampling methods and test approaches are seen, but amongst studies identifying wastewater-human AMR correlations, more…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States and the United Kingdom have both implemented national WGS services [1,2], and in 2016, 26 European countries reported the use of WGS in routine public health practice [3]. The reduction in cost and advancement of portable sequencing technologies has continued to increase accessibility for low-resource settings and low-and middle-income countries [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…On the positive side, fecal shedding of SARS-CoV-2 can be exploited for community surveillance of wastewater or human waste using similar methods that would be required for risk evaluation. 22 , 40 Enteric pathogen, polio, and antimicrobial resistance environmental surveillance could be leveraged, where these have been initiated, 10 , 41 , 42 but sites with no access to sewerage, typically not used for surveillance, must also be included. In high-risk settings, waste and wastewater-based epidemiology could help balance sampling biases inherent in case- and contact-tracing–based human testing for COVID-19 and consequently predict prevalence.…”
mentioning
confidence: 99%